3509 Developing a Leadership Alumni Forum to foster a culture of leadership at Mount Sinai. (27th March 2019) - Gabrilove, Janice Lynn; Fattah, Layla; Bloom, Lisa; Ventura, Cara Della
Abstract : OBJECTIVES/SPECIFIC AIMS: Leadership is an essential and recognized team science competency. To support the development of leadership skills at Mount Sinai, the LEAD (Leadership Emerging in Academic Departments) program, launched in 2016, delivers a structured 12-month blended learning program for junior faculty. The program aims to promote personal and professional leadership capacity, skills and behaviors. Following a competitive application process, 24 participants each year are selected to participate. In its second year, the challenge for the LEAD program leadership is to support alumni in fostering a culture of leadership that extends beyond the 12-month program. In order to promote a leadership community of practice and offer continued support to junior faculty, the LEAD Alumni program aims to bring former LEAD participants together to maintain motivation, share challenges and successes, meet with mentors and role models, and foster an ongoing community of practice that seeks to embed evidenced-based leadership culture at Mount Sinai. METHODS/STUDY POPULATION: The previous two cohorts of LEAD participants were approached to volunteer for the LEAD Alumni Forum working group. Four LEAD alumni came forward to form a self-selected working group. With input from the program leadership, the alumni working group is tasked with organizing regular events that bring the 48 previous LEAD participants together. The events provide the opportunity for individuals with expertise and a passion for leadership to create a supportive environment. This ultimately seeks to increase the transfer and utilization of leadership skills in practice, and promotes a culture of leadership. These alumni events also provide the opportunity for alumni to interact with senior leaders at Mount Sinai, thereby learning from role models within the organization. RESULTS/ANTICIPATED RESULTS: Evaluating learning transfer and culture change is challenging, so a number of proxy measures will provide insight into the success of the Alumni Forum. Firstly, the number of LEAD Capstone projects implemented in practice, and the success of these initiatives, will provide insight into transfer of leadership learning to practice. Secondly, participants will complete a validated survey tool, Leadership Programs Outcome Measure (LPOM), which explores self-reported leadership change at a personal, organizational and community level. Finally, participants will be followed up in the long-term to track promotion, awards, and other formal or informal leadership positions assumed following engagement in the LEAD program and the subsequent LEAD Alumni Forum. DISCUSSION/SIGNIFICANCE OF IMPACT: It is hoped the LEAD Alumni program will enhance the ability of participants to implement leadership knowledge and skills to practice, which may subsequently advance organization and culture change. Fostering a community of practice will further the reach of the LEAD program and as the number of LEAD alumni grows, and the Alumni Forum may provide the supportive environment that allows these individuals to have real impact.